(untitled) (African Journal of Biomedical Research, 2020)
The effect of Human Immunodeficiency Virus (HIV) and possibly Highly Active Antiretroviral Therapy (HAART) on pregnancy and neonatal outcomes has been a controversial issue with some researches reporting no association while others reporting significant association. This study aimed at comparing the pregnancy and neonatal outcomes between Human Immunodeficiency Virus (HIV) positive women and HIV negative women who delivered at University College Hospital (UCH), Ibadan. This study was a cross-sectional study carried out at the University College Hospital, Ibadan Nigeria. The case notes of all the HIV positive pregnant women and their comparison group who delivered in the year 2013(January 1st- December 31st) were retrieved. Data was summarized with frequency tables and mean (SD). Association between categorical variables was analyzed using chi-square test or Fisher test and association between continuous variables were analyzed using independent T-test. A probability value of <0.05 was considered statistically significant. Compared with the HIV negative women the HIV positive women had higher parity (p<0.001), lesser educational qualifications (p=0.004) and lower occupational positions (p<0.001). The differences for selected pregnancy and neonatal outcomes were not statistically significant; antenatal complications, blood loss at delivery, gestational age at delivery, birthweight of the babies, Apgar score, perinatal death and congenital anomalies. The socio-demographic characteristics were different in both groups and highlight need for programs to address these factors